Comparison between stainless steel staples and silk sutures for primary closure of skin in patients undergoing neck dissection: A comparative clinical study - Abhishek Ghosh; Madan Nanjappa; Vaibhav Nagaraj; G C Rajkumar (Wolters Kluwer Medknow Publications, 2015)
Introduction: Comparison between stainless steel staples and silk sutures for primary closure of skin in patients undergoing neck dissection, in context of rapid application, approximation of the skin edges, economy and aesthetics of the resultant scar. Aim: (1) To compare surgical stainless steel staples and silk sutures for primary wound closure, with respect to presence/absence of wound infection and dehiscence (2) To compare the resultant scar following the two different methods of the closure at 3 rd month postoperatively with the help of visual analog scale and analyze the result statistically Design: This study was designed to compare skin closure using staples and silk sutures in patients undergoing neck dissection, using both methods in one-half of the same wound; thus each wound affording its own control. Materials and Methods: The study was conducted on patients requiring collar line incision (high submandibular incision) with or without a cephalad extension of midline lower lip split incision for surgical access, who presented to the Department of Oral and Maxillo-Facial Surgery. (1) Sample size: 10 (2) Study design: Prospective Comparative study (3) Study duration: One and half years (4) Surgical stainless steel staples: Proximate Plus MD 35 W, Ethicon Endo Surgery (5) Sutures: 3-0 Ethiprime NW 5003, Non-Absorbable Surgical Suture, Mersilk-90 cm, Ethicon, (16 mm 3/8 circle cutting needle). Conclusion: It wass concluded that there is no significant difference between the scars observed in the regions of incision which underwent primary closure by two different methods, that is surgical stainless steel staples and 3-0 Mersilk Sutures.